2021
DOI: 10.3390/ma14040821
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Oxide Thin Films Grown on Flexible ITO-Coated PET Substrates

Abstract: Molybdenum oxide thin films were deposited on stiff and flexible substrates by reactive DC magnetron sputtering. Two sets of samples were prepared. The first with different O2/Ar flow rate ratios and the second, fixing the oxygen content, with different time of deposition. As the O2/Ar flow rate ratio varies from 0 up to 0.56, a threshold was found, ranging from crystalline to amorphous nature, and from a nontransparent appearance with metallic-like electrical conductivity to transparent and dielectric behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…With respect to XRR, a developed code to be fully integrated into the MROX main software was developed. Several publications fall into prior versions of the software can be found elsewhere [39,40]. The XRD/XRR measurements were performed on a Bruker D8 AXS diffractometer.…”
Section: Samples and Description Of The Experimental Techniquesmentioning
confidence: 99%
“…With respect to XRR, a developed code to be fully integrated into the MROX main software was developed. Several publications fall into prior versions of the software can be found elsewhere [39,40]. The XRD/XRR measurements were performed on a Bruker D8 AXS diffractometer.…”
Section: Samples and Description Of The Experimental Techniquesmentioning
confidence: 99%
“…34 These binding energy peaks indicate that Mo ions existed in the 6+ oxidation state. 34,35 In the comparative survey spectra, the a-Ni 0.95 Cu 0.05 MoO 4 @CC sample showed a little intense peak at ∼950 eV when compared to the pristine a-NiMoO 4 @CC sample. In general, Cu 2p peaks existed between 930 and 960 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Such results have been also observed in non-carbon-based materials. Marciel et al [39] showed that MoO x thin film grown at a higher O 2 /Ar flow rate is more resistive compared to that grown in the absence of O 2 . It is clear that the carbon content is directly proportional to the sheet resistance and indirectly proportional to the degree of amorphousity.…”
Section: Electric Studiesmentioning
confidence: 99%